2014
DOI: 10.1159/000360307
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF Therapy in Myopic Choroidal Neovascularization: Long-Term Results

Abstract: Purpose: To evaluate the medium- and long-term efficacy of anti-VEGF agents in the treatment of choroidal neovascularization secondary to pathologic myopia (mCNV). Methods: We performed a retrospective analysis of patients with mCNV who had been treated with intravitreous anti-VEGF for at least 2 years. The best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were compared before and after the treatment. The number of injections per year was also assessed. Results: The results were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…It is known, that in addition to baseline VA, the prognostic factors for VA outcome after anti-VEGF therapy in patients with mCNV include age, CNV size and location, presence of chorioretinal atrophy, choroidal thickness, and recurrence of mCNV [26,28,[33][34][35][36][37]. Longterm follow-up of mCNV is required since mCNV can recur in patients after discontinuing anti-VEGF treatment [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is known, that in addition to baseline VA, the prognostic factors for VA outcome after anti-VEGF therapy in patients with mCNV include age, CNV size and location, presence of chorioretinal atrophy, choroidal thickness, and recurrence of mCNV [26,28,[33][34][35][36][37]. Longterm follow-up of mCNV is required since mCNV can recur in patients after discontinuing anti-VEGF treatment [38].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that patients with lower initial BCVA exhibit greater visual gains with anti-VEGF treatment, but a higher baseline BCVA can result in a higher final BCVA after treatment. 19 , 22 , 33 , 34 Furthermore, some studies have shown that age at baseline is negatively associated with both BCVA outcome and BCVA change in patients with mCNV after treatment with anti-VEGF therapy. 23 , 33 In the Chinese study, the mean baseline age was 10 years younger than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Freitas-da-Costa et al 56 reported the long-term results of anti-VEGF therapy in mCNV. The mean change from baseline BCVA was significant at 2 years (+8.6 letters; P <0.001) and this gain remained significantly stable for a period of 5 years.…”
Section: Current Treatment Options For Myopic Choroidal Neovascularizmentioning
confidence: 99%